iPla2β deficiency in mice fed with MCD diet does not correct the defect of phospholipid remodeling but attenuates hepatocellular injury via an inhibition of lipid uptake genes - Zhu, Xingya; Gan-Schreier, Hongying; Otto, Ann-Christin; Cheng, Yuting; Staffer, Simone; Tuma-Kellner, Sabine; Ganzha, Alexandra; Liebisch, Gerhard; Chamulitrat, Walee (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2019)
Group VIA calcium-independent phospholipase A2 (iPla2β) is among modifier genes of non-alcoholic fatty liver disease which leads to non-alcoholic steatohepatitis (NASH). Consistently, iPla2β deletion protects hepatic steatosis and obesity in genetic ob/ob and obese mice chronically fed with high-fat diet by replenishing the loss of hepatic phospholipids (PL). As mouse feeding with methionine- and choline-deficient (MCD) diet is a model of lean NASH, we tested whether iPla2β-null mice could still be protected since PL syntheses are disturbed. MCD-diet feeding of female wild-type for 5weeks induced hepatic steatosis with a severe reduction of body and visceral fat weights concomitant with a decrease of hepatic phosphatidylcholine. These parameters were not altered in MCD-fed iPla2β-null mice. However, iPla2β deficiency attenuated MCD-induced elevation of serum transaminase activities and hepatic expression of fatty-acid translocase Cd36, fatty-acid binding protein-4, peroxisome-proliferator activated receptorγ, and HDL-uptake scavenger receptor B type 1. The reduction of lipid uptake genes was consistent with a decrease of hepatic esterified and unesterified fatty acids and cholesterol esters. On the contrary, iPla2β deficiency under MCD did not have any effects on inflammasomes and pro-inflammatory markers but exacerbated hepatic expression of myofibroblast α-smooth muscle actin and vimentin. Thus, without any rescue of PL loss, iPla2β inactivation attenuated hepatocellular injury in MCD-induced NASH with a novel mechanism of lipid uptake inhibition. Taken together, we have shown that iPla2β mediates hepatic steatosis and lipotoxicity in hepatocytes in both obese and lean NASH, but elicits exacerbated liver fibrosis in lean NASH likely by affecting other cell types.
Gesehen am 21.08.2019